2019
DOI: 10.1002/jeab.551
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of resurgence following functional communication training conducted in alternative antecedent contexts via telehealth

Abstract: Treatments based on differential reinforcement may inadvertently increase the recurrence of problem behavior in the face of challenges because reinforcers for appropriate behavior occur in the same context as problem behavior. The current study evaluated one potential approach to mitigating these problems with differential reinforcement treatments based on behavioral momentum theory. Specifically, appropriate behavior was trained in contexts without a history of reinforcement prior to intervening with problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
1
12
0
2
Order By: Relevance
“…An additional twelve studies utilized telehealth via VC to deliver functional communication training (FCT) after functional analyses that were also delivered via telehealth (Benson et al, 2018;Gerow et al, 2021a, b;Lindgren, 2016Lindgren, , 2020Machalicek et al, 2016;O'Brien et al, 2021;Schieltz et al, 2018;Simacek et al, 2017;Suess et al, 2014Suess et al, , 2016Suess et al, , 2020Wacker et al, 2013). Studies varied on the design and method used to evaluate the implementation of the FCT (e.g., randomized control trial, single-subject design) but the coaching of parents via VC during functional analysis and FCT sessions was utilized across studies.…”
Section: Functional Communication Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional twelve studies utilized telehealth via VC to deliver functional communication training (FCT) after functional analyses that were also delivered via telehealth (Benson et al, 2018;Gerow et al, 2021a, b;Lindgren, 2016Lindgren, , 2020Machalicek et al, 2016;O'Brien et al, 2021;Schieltz et al, 2018;Simacek et al, 2017;Suess et al, 2014Suess et al, , 2016Suess et al, , 2020Wacker et al, 2013). Studies varied on the design and method used to evaluate the implementation of the FCT (e.g., randomized control trial, single-subject design) but the coaching of parents via VC during functional analysis and FCT sessions was utilized across studies.…”
Section: Functional Communication Trainingmentioning
confidence: 99%
“…After the implementation of FCT with remote coaching and training via telehealth, child problem behaviors were reduced in 11 studies (Benson et al, 2018;Gerow et al, 2021a, b;Lindgren et al, 2016Lindgren et al, , 2020Machalicek et al, 2016;O'Brien et al, 2021;Schieltz et al, 2018;Suess et al, 2014Suess et al, , 2016Suess et al, , 2020Wacker et al, 2013). One particular study focused on reducing the resurgence of problem behaviors once they were reduced significantly and demonstrated that remote coaching of FCT can accomplish this both effectively and more rapidly than previous research (Suess et al, 2020). Further, parents were able to conduct a functional analysis and the intervention strategies derived from this reduced the child's problem behaviors (Machalicek et al, 2016;Suess et al, 2016).…”
Section: Functional Communication Trainingmentioning
confidence: 99%
“…The most common version of telehealth services represented in the published literature is a caregiver telehealth coaching model, which involves a clinician providing training via synchronous videoconferencing to another person (e.g., parent, teacher, technician) at a distant site to deliver services in‐person to the client (Council of Autism Service Providers [CASP], 2020a; Lerman et al, 2020). This model has been used for functional behavior assessments (Barretto et al, 2006; Benson et al, 2018; Boisvert et al, 2010), preference assessments (Higgins et al, 2017), behavior reduction procedures (Hall et al, 2020; Lindgren et al, 2016; Monlux et al, 2019; Suess et al, 2016; Suess et al, 2020; Unholz‐Bowden et al, 2020; Wacker et al, 2013a; Wacker et al, 2013b), and interventions to build language, social, and daily living skills (Akemoglu et al, 2020; Barkaia et al, 2017; Ferguson et al, 2019; Ingersoll et al, 2016; McLay et al, 2020; Wainer & Ingersoll, 2015). A telehealth model commonly applied in clinical settings is a partial in‐person telehealth model whereby ABA services are rendered in‐person by a trained technician, with clinical oversight provided by a behavior analyst via real‐time, synchronous videoconference modality (CASP, 2020b).…”
mentioning
confidence: 99%
“…The majority of the ASD papers reported that treatment was clinically effective in improving caregiver knowledge, caregiver competence, and child participation (6/18, 33%) [38][39][40][41][42]45], increasing communication responses (2/18, 11%) [34,45], and reducing problem behaviors (5/18, 28%) [31,32,[35][36][37]. We found 1 (5%) paper [33] that discussed 2 young children with ASD who underwent functional communication training, but this was unsuccessful in reducing problem behaviors.…”
Section: Clinical Effectivenessmentioning
confidence: 86%
“…Of these 17 papers, 6 (35%) reported on providing telehealth-delivered functional analysis and communication training to parents [31][32][33][34][35][36], and 1 (6%) reported on using telehealth-delivered functional analysis to train a health care professional [37]. These studies mainly consisted of case studies or case series (6/7, 86%) that used a multiple baseline experimental design and had a QR of 3 [35] or 4 [31,32,34,36,37]. Another paper (1/7, 14%) reexamined 2 nonresponding participants' data from an RCT (QR=4) [33].…”
Section: Summary Of Asd Treatment Papersmentioning
confidence: 99%